PENGARUH METODE PRAKTIKUM BERBASIS LINGKUNGAN TERHADAP PEMAHAMAN KONSEP PADA MATERI LAJU REAKSI - Fajriati Fajriati; Husna Amalya Melati; Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe aims of this research were to determine  whether there is a difference in understanding the concept of students class taught by environmental-based practice method with taught convensional  student class on the reaction rate material and determine of the influence of the use of practice method based on the understanding of the concept of students on the reaction rate material. This form of research is a quasi experiment with the design of Nonequivalent Control Group Design. The sample of this research is class XI IPA which is divided into two groups, the first group as the experimental class and the second group as the control class. The worksheet were used are instruments and concept comprehension test. Based on the U Mann-Whitne testwith significance level α = 5% indicates that there is a difference between understanding the concept of students taught by environment-based practice method with those taught without using environment-based practicum methods. The value of effect size  is 1.06  with high category and gave the contribution 35,54%, it means the use of environment-based practice method influence the students' concept of understanding. Keywords: Environmental Based Practicum Method, Concept Understanding,Reaction Rate